Effect of Hemodiafiltration on the Progression of Neuropathy with Kidney Failure: A Randomized Controlled Trial. Issue 9 (September 2021) - Kang, Amy; Arnold, Ria; Gallagher, Martin; Snelling, Paul; Green, Julianne; Fernando, Mangalee; Kiernan, Matthew C.; Hand, Samantha; Grimley, Kim; Burman, Jenny; Heath, Anne; Rogers, Kris; et al.
Visual Abstract: Abstract : Background and objectives: Neuropathy is a common complication of kidney disease that lacks proven disease-modifying treatments. Hemodiafiltration improves clearance of uremic toxins and is associated with better nerve function than hemodialysis. We aimed to determine whether hemodiafiltration reduces the progression of neuropathy in people receiving hemodialysis. Design, setting, participants, & measurements: The Filtration in the Neuropathy of End-Stage Kidney Disease Symptom Evolution (FINESSE) study was an open-label, blinded end point assessment, controlled trial that randomized maintenance hemodialysis recipients to hemodiafiltration or high-flux hemodialysis for 48 months or until death or cessation of dialysis at four study centers. The primary outcome was the mean change in the yearly modified total neuropathy score from baseline, with time points weighted equally. Results: A total of 124 participants were randomized and followed for a mean of 41 months. At baseline, neuropathy was present in 91 (73%) participants (modified total neuropathy score greater than or equal to two), and 38 (31%) had moderate to severe neuropathy (modified total neuropathy score 9–28). Convection volume in the hemodiafiltration arm was a median of 24.7 (interquartile range, 22.4–26.5) L. The mean modified total neuropathy score (SEM) worsened by 1.7 (0.4)/28 and 1.2 (0.4)/28 in the hemodiafiltration and hemodialysis groups, respectively, with a mean difference of 0.5 (95% confidence interval, −0.7 to 1.7; P =0.37). There was no difference in survival (hazard ratio, 1.24; 95% confidence interval, 0.61 to 2.51; log rank P =0.55) or any of the prespecified adverse events. There was no difference between groups in the number of participants who suffered an adverse event adjusted by follow-up time (relative risk, 1.05; 95% confidence interval, 0.83 to 1.32; P =0.68). Conclusions: Neuropathy is still a common complication of kidney disease without disease-altering therapy. Hemodiafiltration did not affect neuropathy progression compared with hemodialysis. Clinical Trial registry name and registration number: Filtration in the Neuropathy of End-Stage Kidney Disease Symptom Evolution (FINESSE), ACTRN12609000615280